The Effectiveness of a Four-Week Digital Physiotherapy Intervention to Improve Functional Capacity and Adherence to Intervention in Patients with Long COVID-19. - Estebanez Pérez, María José; Pastora-Bernal, José Manuel; Martín-Valero, Rocío (MDPI, 2022)
Long COVID-19 has been defined as the condition occurring in individuals with a history of probable or confirmed SARS-CoV-2 infection, with related symptoms lasting at least 2 months and not explainable by an alternative diagnosis. The practice of digital physiotherapy presents itself as a promising complementary treatment method to standard physiotherapy, playing a key role in the recovery of function in subjects who have passed the disease and who maintain some symptomatology over time. The aims of this research are to explore the effect of a digital physiotherapy intervention on functional recovery in patients diagnosed with Long COVID-19 and to identify the level of adherence to the treatment carried out. A quasi-experimental pre-post study assessed initially and at the end of the 4-week intervention the functional capacity (1-min STS and SPPB) and the adherence (software) of a total of 32 participants. After the 4-week digital physiotherapy practice intervention with an individualised and customise exercise programme, a statistically significant improvement was observed (p < 0.05) with a small to medium effect size, high adherence rates and values above the minimal clinically important difference (MCID). We consider our intervention feasible, safe and consistent with our objectives. However, further randomised clinical trials and studies with larger samples are needed to draw extrapolable conclusions. Trial registration NCT04742946.
Keywords: Fisioterapia - Innovaciones tecnológicas; Rehabilitación - Innovaciones tecnológicas; Long COVID-19; Digital physiotherapy practice; Functional capacity; Therapeutic adherence; Telerehabilitation